2010
DOI: 10.1038/icb.2010.94
|View full text |Cite
|
Sign up to set email alerts
|

CD40 engagement on dendritic cells induces cyclooxygenase‐2 and EP2 receptor via p38 and ERK MAPKs

Abstract: We have previously reported that cyclooxygenase (COX)-2-derived prostaglandin (PG)E2 critically regulates dendritic cell (DC) inflammatory phenotype and function through EP2/EP4 receptor subtypes. As genes activated by CD40 engagement are directly relevant to inflammation, we examined the effects of CD40 activation on inflammatory PGs in murine bone marrow-derived DC (mBM-DC). We showed for the first time that activation of mBM-DC with agonist anti-CD40 monoclonal antibody (anti-CD40 mAb) dose dependently indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 53 publications
(112 reference statements)
1
18
0
Order By: Relevance
“…HIV-1 directly affects dendritic cells (DC) and leads to dysfunction of immune system manifested by increased levels of inflammatory cytokines, chemokines and neurotoxin such as quinolinic acid and arachidonic acid (AA) [9], [10]. Increasing evidence suggests that DCs play a major role in the defense against HIV infection and illicit drug such as cocaine [11][13].…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 directly affects dendritic cells (DC) and leads to dysfunction of immune system manifested by increased levels of inflammatory cytokines, chemokines and neurotoxin such as quinolinic acid and arachidonic acid (AA) [9], [10]. Increasing evidence suggests that DCs play a major role in the defense against HIV infection and illicit drug such as cocaine [11][13].…”
Section: Introductionmentioning
confidence: 99%
“…The rate-limiting enzyme in PGE2 synthesis is COX-2. In DCs, COX-2 can be induced by bacterial lipopolysaccharide, 40 mimicking bacterial infection, or CD40 triggering, 41 which may occur during physiological interactions between APC and T cells during antigen presentation. Proinflammatory cytokines, especially TNF-alpha, can also induce COX-2-derived PGE2.…”
Section: Pge2 Production By Dcs But Not By Nk Cellsmentioning
confidence: 99%
“…Genes activated by CD40 engagement are directly relevant to inflammation. In a recent study, Harizi et al [39] showed that CD40 engagement on dendritic cells induces COX-2 via p38 and ERK MAPKs. COX-2 is highly expressed in macrophages of inflamed tissues, which can be activated via CD40 to produce tissue factor [41], thereby enhancing the chronic inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…CD40 is a cell membrane-spanning protein of 50 kDa which is expressed on B lymphocytes, macrophages, dendritic cells and fibroblasts [39,40]. Genes activated by CD40 engagement are directly relevant to inflammation.…”
Section: Discussionmentioning
confidence: 99%